1987
DOI: 10.2118/14713-pa
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Instability on Relative Permeability Curves Obtained by the Dynamic-Displacement Method

Abstract: 5PE )47/3 summary.A study was undertaken to investigate how instability would affect the oii[water relative permeability curves bhtained by the. dynamic-displacement method. In this method, stable Buckley-Leverett displacement theorj is used to calculate relative permeability cuties from coreflood dsta, Thus, to obtain the true relative permeability curves by the dynarnic-disp~cement method, the coreflocd must he stable. However, the method frequently has been applied to umstable core ftoods. The consequence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

1991
1991
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(18 citation statements)
references
References 6 publications
0
18
0
Order By: Relevance
“…To overcome well-known difficulties in measuring relative permeability curves under low IFT, several attempts were made (Fulcher et al 1985;Peters and Khataniar 1987;Chisholm et al 1990), involving either increasing viscous forces in displacing fluids or increasing the capillary number. However, large increase in the viscosity of the displacing, aqueous phase may lead to too large decrease in displacing rates or mobility.…”
Section: Introductionmentioning
confidence: 99%
“…To overcome well-known difficulties in measuring relative permeability curves under low IFT, several attempts were made (Fulcher et al 1985;Peters and Khataniar 1987;Chisholm et al 1990), involving either increasing viscous forces in displacing fluids or increasing the capillary number. However, large increase in the viscosity of the displacing, aqueous phase may lead to too large decrease in displacing rates or mobility.…”
Section: Introductionmentioning
confidence: 99%
“…Also, the flow regime characterized by the laboratory experiment may not match that in the field. 3 If suitable estimates from core samples are not available, relative permeability curves may be obtained with empirical methods 2 or from experiences with similar reservoirs. Of course, these types of estimates suffer from the large uncertainty commonly associated with empirical models.…”
Section: Current Estimation Methodsmentioning
confidence: 99%
“…Stokes et al (1986Stokes et al ( ) 1986 The authors demonstrated that in the medium which preferentially wet by displaced fluid, the width of Page 18 of 49 A c c e p t e d M a n u s c r i p t 19 fingers is comparable by the pore size and independent to other parameters. Peters and Khataniar (1987) 1987…”
Section: Researchermentioning
confidence: 99%